2008
DOI: 10.1086/591445
|View full text |Cite
|
Sign up to set email alerts
|

Giant Chromospheric Anemone Jet Observed with Hinode and Comparison with Magnetohydrodynamic Simulations: Evidence of Propagating Alfvén Waves and Magnetic Reconnection

Abstract: Hinode discovered a beautiful giant jet with both cool and hot components at the solar limb on 2007 February 9. Simultaneous observations by the Hinode SOT, XRT, and TRACE 195Å satellites revealed that hot (∼ 5 × 10 6 K) and cool (∼ 10 4 K) jets were located side by side and that the hot jet preceded the associated cool jet (∼ 1 − 2 min.). A current-sheet-like structure was seen in optical (Ca II H), EUV (195Å), and soft X-ray emissions, suggesting that magnetic reconnection is occurring in the transition regi… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

16
161
2

Year Published

2008
2008
2021
2021

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 178 publications
(179 citation statements)
references
References 40 publications
(52 reference statements)
16
161
2
Order By: Relevance
“…This results in the ejection of cool plasma (10 000 K) that had been supported by the field. Magnetohydrodynamic simulations of this scenario describe the observations well (Yokoyama & Shibata 1995;Nishizuka et al 2008;Moreno-Insertis et al 2008). Ejected jet material accelerated by the J × B force will have a velocity of the order of the Alfvén speed.…”
Section: Introductionmentioning
confidence: 73%
“…This results in the ejection of cool plasma (10 000 K) that had been supported by the field. Magnetohydrodynamic simulations of this scenario describe the observations well (Yokoyama & Shibata 1995;Nishizuka et al 2008;Moreno-Insertis et al 2008). Ejected jet material accelerated by the J × B force will have a velocity of the order of the Alfvén speed.…”
Section: Introductionmentioning
confidence: 73%
“…The speeds of the outflows were estimated to be in the range from 200 to 800 km s −1 . Hot jets observed in soft X-rays precede cool jets observed in the optical band (Nishizuka et al 2008).…”
Section: Introductionmentioning
confidence: 93%
“…They interpreted the increase of the radiance in the cooler spectral lines as emitted from the falling back plasma of the cooling down jet. Nishizuka et al (2008) reported on simultaneous cool emission (∼10 4 K) in Ca ii H images from the Solar Optical Telescope (SOT) onboard Hinode and hot emission (1.3 × 10 6 K) in Fe xii 195 Å images from the Extreme-ultraviolet Imaging Telescope (EIT) and movie are only available in electronic form at http://www.aanda.org onboard the Solar and Heliospheric Observatory (SoHO) as well as in X-ray Telescope (XRT) images (Al_poly filter with a temperature response with a maximum at 5 × 10 6 K) from a "giant" jet. From their observations of a current-sheet-like structure seen in all three instruments, they concluded that magnetic reconnection is occurring in the transition region or upper chromosphere.…”
Section: Introductionmentioning
confidence: 99%